Cakesthetic / Muhammad Aqil Najmi Mohd Anuar ...[et al.] - Mohd Anuar, Muhammad Aqil Najmi; Osman Ali, Nursarafina; Zaidi, Mursyid; Roslani, Azdrieyana Azreen; Azmi, Afrina Syafiah; Ab Rahman, Muhammad Faiz Fikri (2022)
This business plan is about the Cakesthetic which is of the business nature is selling many varieties of cakes such as mini pavlova, korean cakes, batik cake indulgence, Nutella brownies and Biscoff cheesecake. Our mission is to serve our customer with the top quality of cakes that going along to the best customer service in town. Our business is a café concept bakery with the mesmerizing design of the store that can give the instaworthy types of pictures to our customers while they are buying our cakes. Cakesthetic is a partnership company with 6 members that contributed to the company. Our projection of the business is to be one of the famous and best bakery cafés in Malaysia. At the same time, we want to build our name across the Malaysian market in food and beverages industries. Our target market is the local residents, parents, working adult and teenagers, students, and cake enthusiast. Our specialties are on the design and concept of the café with the handmade and skilled bakers of ours, it will give the best experience to our customers and make our business stand out from the others. Our business Cakesthetic will give the profit to the business organization because this business plan is the guidelines for us to make the organization run on the right track. All of the partnership members have their own responsibility in the management of the business. The general manager will be the leader of all management team to leads the organization achieve its goal. The administration management will cover on how much workers do we need and the roles of every manpower and scheduling. The marketing team will reach the target market with various way of marketing method such as advertising and promotion. The operation manager will give the details of the product used and the machinery needed for production of the cakes. The final key components of management are the financial manager who is in responsible to take care the organization financial to ensure that the organization use the budget allocated efficiently and have a good financial structure to attracts more investors to invest in our business.